Aryl Hydrocarbon Receptor Signaling Prevents Activation of Hepatic Stellate Cells and Liver Fibrogenesis in Mice - Yan, Jiong; Tung, Hung-Chun; Li, Sihan; Niu, Yongdong; Garbacz, Wojciech G.; Lu, Peipei; Bi, Yuhan; Li, Yanping; He, Jinhan; Xu, Meishu; Ren, Songrong; Monga, Satdarshan P.; et al. (Gastroenterology (New York, N.Y. 1943), 2019)
The role of aryl hydrocarbon receptor (AhR) in liver fibrosis is controversial because loss and gain of AhR activity both lead to liver fibrosis. The goal of this study was to investigate how the expression of AhR by different liver cell types, hepatic stellate cells (HSCs) in particular, affects liver fibrosis in mice. We studied the effects of AhR on primary mouse and human HSCs, measuring their activation and stimulation of fibrogenesis using RNA-sequencing analysis. C57BL/6J mice were given the AhR agonists 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) or 2-(1′H-indole-3′-carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE); were given carbon tetrachloride (CCl4); or underwent bile duct ligation. We also performed studies in mice with disruption of Ahr specifically in HSCs, hepatocytes, or Kupffer cells. Liver tissues were collected from mice and analyzed by histology, immunohistochemistry, and immunoblotting. AhR was expressed at high levels in quiescent HSCs, but the expression decreased with HSC activation. Activation of HSCs from AhR-knockout mice was accelerated compared with HSCs from wild-type mice. In contrast, TCDD or ITE inhibited spontaneous and transforming growth factor β–induced activation of HSCs. Mice with disruption of Ahr in HSCs, but not hepatocytes or Kupffer cells, developed more severe fibrosis after administration of CCl4 or bile duct ligation. C57BL/6J mice given ITE did not develop CCl4-induced liver fibrosis, whereas mice without HSC AhR given ITE did develop CCl4-induced liver fibrosis. In studies of mouse and human HSCs, we found that AhR prevents transforming growth factor β–induced fibrogenesis by disrupting the interaction of Smad3 with β-catenin, which prevents the expression of genes that mediate fibrogenesis. In studies of human and mouse HSCs, we found that AhR prevents HSC activation and expression of genes required for liver fibrogenesis. Development of nontoxic AhR agonists or strategies to activate AhR signaling in HSCs might be developed to prevent or treat liver fibrosis. [Display omitted]